Ambulatory Blood Pressure Monitoring in Resistant Hypertension - Dimitrios Syrseloudis; Ioannis Andrikou; Eirini Andrikou; Kyriakos Dimitriadis; Christodoulos Stefanadis (International Journal of Hypertension)
ABPM constitutes a valuable tool in the diagnosis of RH. The identification of white coat RH and masked hypertension (which may fulfill or not the definition of RH) is of great importance in the clinical management of such patients. Moreover, the various ABPM components such as average BP values, circadian BP variability patterns, and ambulatory BP-derived indices, such as ambulatory arterial stiffness index (AASI), add significantly to the risk stratification of RH. Lastly, ABPM may indicate the need for implementation of specific therapeutic strategies, such as chronotherapy, that is, administration-time dependent therapy, and the evaluation of their efficacy.